Comparison of failure rates of CU t 380 A and CU safe 300 IUDs four years after insertion - farahnaz Changavi (Yafteh, 2007)
Changavi F1, janani F1, Asti P1, Akbari S2 1. Instructor, Department of midwifery, Faculty of nursing and midwifery, Lorestan University of Medical Sciences 2. Instructor, Department of gynecology, Faculty of medicine, Lorestan University of Medical Sciences Abstract Background: IUD is a useful and effective tool for family planning. Different kinds of this equipment are available at the market, but currently the most commonly used one in our country is CU T380A. Previous studies have shown that CU safe 300 is more effective and associated with less complications than CU t380A, thus it is more acceptable by users. The aim of this study was to determine and compare failure rate of CU T380A and CU safe 300 IUDS, four years after insertion. Materials and methods: The present research is a cohort study carried out on 246 women who referred to health clinics of Khorramabad four years ago. These women divided into two equal groups. One group used CU T380A and the other group used CU safe 300. The rate of unwanted delayed complications such as spontaneous bleeding, pregnancy and spontaneous repelling of the IUDs were assessed by a questionnaire. Data were analyzed by Chi square and paired T test. Results: Failure rate of CU T380A was more than CU safe 300. Statistical tests showed significant differences between these two groups. Conclusion: This study shows that new IUD (CU safe 300 ) which are smaller in size have less Failure rate and more acceptable by women, so their use is suggested in health clinics. Key words: